High resolution BrainPET combined with simultaneous MRI - Herzog, H.; Langen, K.-J.; Weirich, C.; Rota Kops, E.; Kaffanke, J.; Tellmann, L.; Scheins, J.; Neuner, I.; Stoffels, G.; Fischer, K.; Caldeira, L.; Coenen, H. H.; Shah, N. J. (Nuklearmedizin - NuclearMedicine, 2011)
After the successful clinical introduction of PET/CT, a novel hybrid imaging technology combining PET with the versatile attributes of MRI is emerging. At the Forschungszentrum Jülich, one of four prototypes available worldwide combining a commercial 3T MRI with a newly developed BrainPET insert has been installed, allowing simultaneous data acquisition with PET and MRI. The BrainPET is equipped with LSO crystals of 2.5 mm width and Avalanche photodiodes (APD) as readout electronics. Here we report on some performance characteristics obtained by phantom studies and also on the initial BrainPET studies on various patients as compared with a conventional HR+ PET-only scanner. Material, methods: The radiotracers [18F]-fluoroethyl- tyrosine (FET), [11C]-flumazenil and [18F]-FP-CIT were applied. Results: Comparing komthe PET data obtained with the BrainPET to those of the HR+ scanner demonstrated the high image quality and the superior resolution capability of the BrainPET. Furthermore, it is shown that various MR images of excellent quality could be acquired simultaneously with BrainPET scans without any relevant artefacts. Discussion, conclusion: Initial experiences with the hybrid MRI/BrainPET indicate a promising basis for further developments of this unique technique allowing simultaneous PET imaging combined with both anatomical and functional MRI.
Keywords: Positron emission tomography; magnetic resonance imaging; PET; MRI; PET/MRI; MRPET; multimodality; hybrid imaging